Evidentiality, Learning Events and Spatiotemporal Distance: The View from Bulgarian. (14th January 2016) - Koev, Todor
Abstract: The grammatical category of evidentiality is traditionally conceived as marking the 'information source' for the claim described by the sentence (see e.g. Anderson 1986 ; Willett 1988 ; Aikhenvald 2004 ). This article defends the view that evidentiality need not be a semantic primitive but can rather be pragmatically derived from the spatiotemporal distance between the event described by the sentence and the 'learning event', that is the event of the speaker acquiring the relevant evidence for her claim. While the empirical focus is on the Bulgarian evidential -l, this work adds to similar proposals about evidential markers in typologically unrelated languages (see Nikolaeva 1999 ; Fleck 2007 ; Speas 2010 ; Kalsang et al . 2013 ; Lee 2013 ). The view of evidentiality as a spatiotemporal distance undermines the claim that evidential sentences in Bulgarian have modal force (pace Izvorski 1997 ; Smirnova 2013 ) and correctly predicts that speakers are typically committed to the core proposition described by evidential sentences. The article also discusses the not-at-issue discourse status and projection behavior of the evidential implication, suggesting that evidential meanings belong to the broader class of 'conventional implicatures', in the sense of Potts (2005) . The formal proposal, couched in an update semantics, successfully captures not only the meaning of the evidential marker but also the discourse properties of evidential sentences in Bulgarian.